Ôkatrarana Ceremony from Eastern Madagascar: Exploring the Soundscape Between Worlds - Smoluch, Łukasz (Interdisciplinary Studies in Musicology, 2026)
This paper presents preliminary findings from field research conducted in 2024 on the island of Sainte Marie (Nosy Boraha), Madagascar, focusing on the ôkatrarana ceremony – a ritual of exhumation and reburial rooted in Malagasy ancestral traditions. The study is concerned with the performative and sonic aspects of ceremony, and specifically the role of singing, drumming, and dancing in mediating the passage between the world of the living and the world of the dead. This article argues that music functions as a ‛ritual tool’ that gives structure to time frame of the ceremony, guides emotions, and strengthens social cohesion. The bingy bé performance, characterized by polyrhythmic drumming and responsorial singing, is analyzed as a key element in generating collective affect and spiritual transformation. This study contributes also to a broader discussion on the connections between music, rituals, and cultural memory in the Indian Ocean region.